A Qualitative Case Study on Fintech-Driven Modernization of Capital Market Infrastructure - Untung Rahardja; Ratna Utami Wijayanti; Yunita Christy; Gabriel Fransiso (Pandawan Sejahtera Indonesia, 2026)
By addressing inefficiencies, high operating costs, and transparency constraints in conventional systems, this study investigates the role of Financial Technology (fintech) in modernizing capital market infrastructure. The study examines the impact of cloud computing, Artificial Intelligence (AI), machine learning, and Distributed Ledger Technology (DLT) on pre-trade, trade, and post-trade processes using a qualitative case study approach and thematic analysis of secondary data from exchanges, fintech companies, industry reports, and regulatory documents. Unlike previous studies that mainly focus on fintech adoption in general financial services or individual technologies, this study provides an integrated analysis of multiple fintech technologies within capital market infrastructure modernization. The findings show that fintech significantly improves post-trade efficiency by reducing operational risks, accelerating settlement processes, and minimizing reliance on intermediaries. Cloud-based infrastructure enhances scalable data analytics and market accessibility, while AI and machine learning strengthen market surveillance and risk management through real-time monitoring and early detection of anomalous trading activities. Despite these benefits, implementation remains constrained by institutional readiness, cybersecurity risks, and regulatory complexity. The study highlights the importance of collaboration among regulators, traditional financial institutions, and fintech firms to ensure sustainable integration and effective risk mitigation. Taken together, the findings indicate that fintech plays a crucial role in creating a more efficient, transparent, and resilient capital market infrastructure.